Компьютерное моделирование иерархической структуры коммуникационной сети с дискретными многопродуктовыми потоками - Трофимчук, А.Н.; Васянин, В.А. (Управляющие системы и машины, 2016)
Предложена компьютерная технология моделирования иерархической структуры и схемы сортировки потоков в коммуникационной сети. Рассмотрены принципы организации сортировки и распределения потоков в иерархической трехуровневой сети. Сформулирована математическая модель задачи и описана демонстрационная программа ее решения, приведен числовой пример проектирования автотранспортной сети перевозок мелких партий грузов. Запропоновано комп'ютерну технологію моделювання ієрархічної структури і схеми сортування потоків в комунікаційній мережі. Розглянуто принципи організації сортування і розподілу потоків в ієрархічній трирівневій мережі. Сформульовано математичну модель задачі і описано демонстраційну програму для її розв’язання, подано числовий приклад проектування автотранспортної мережі перевезень дрібних партій вантажів. Introduction. The computer technology to modeling a hierarchical structure and a flow sorting scheme in communications network are considered. The computer program is the part of the software tools of automated information and analytical decision support system (AIA DSS), which is being developed at the Institute of Telecommunications and Global Information Space of the NAS of Ukraine. The organization principles of sorting and flows distribution in a hierarchical network are given. Purpose. The research purpose is to improve the functioning of the projected communication networks at decrease expense of the scarce material, raw materials, energy, financial and human resources. The increased efficiency is achieved by using the methodology of mathematical modeling and optimization of the discrete flows processing and distribution, a set of information measures, an analytical support and an automate the decision-making procedures in the management of flows. Methods. The mathematical model of the optimization network structure problem and a flow sorting scheme are given. A problem solving algorithms are based on the discrete analog of the local descent method, when the neighborhoods of a metric space of feasible solutions are selected from the heuristic considerations taking into account the peculiarities of the solved problem. Result. A program of modeling a hierarchical structure of the communication network, consisting from scenarios action of the designer and the software system at selection of the structure, of input data and parameters of the designed network is presented. The program runs in an interactive mode, and allows you to calculate the basic technical and economic parameters of the network functioning while changing a topology, hierarchical structure, values of flows, and other source data, parameters and constraints of the transport model. As an example, the results of the transport network design with small lot cargo are given. Conclusion. The proposed computer technology of the problem solution with the hierarchical structure of the communication network and scheme sorting of multicommodity flows, allows you to simulate various network options and from the family of received results choose the best option based on the purpose function selection and the adopted constraints. The technical and economic indicators of the network functioning at the predicted values of flow allow to estimate the cost of the additional resources and plan the magnitude of the required investment for the modernization and construction of its structural elements. Ultimately, the use of the proposed software tools for networks design makes it possible to increase the efficiency of their functioning by optimizing the use of the existing resources and reduce operating costs of the processing and transportation flows.